Volatility analysis of broiler chicken prices in the ramadhan period: a strategic food perspective - Meilany, Shinta Ardita; Sa'diyah, Ana Arifatus; Wulandari, Ayu (Journal of Agricultural Socio-Economics (JASE), 2025)
The price volatility of broiler chicken, a strategic food commodity in Indonesia, becomes a critical issue that escalates significantly during each Ramadan period. This annual phenomenon negatively impacts consumer purchasing power and the sustainability of culinary MSMEs. This study aims to analyse the patterns and measure the persistence level of broiler chicken price volatility to understand the market dynamics during this high-demand period. Using weekly time-series data from the National Strategic Food Price Information Centre (PIHPS) from March 2017 to April 2023, this research applies the Generalised Autoregressive Conditional Heteroscedasticity (GARCH) model. The analysis begins with the ADF stationarity test, the ARMA model identification, and the ARCH effect test to validate the use of the GARCH model. The results show that the price data is stationary at the level and exhibits a significant ARCH effect. The GARCH (1,1) model was selected as the best fit for capturing volatility dynamics. The estimation results indicate the presence of volatility clustering with a high degree of persistence (α + β = 0.743). The larger GARCH coefficient (β = 0.485) compared to the ARCH coefficient (α = 0.258) shows that past volatility has a stronger effect on current price changes than new events do. A high level of persistence implies that a price shock will not dissipate quickly, suggesting that reactive, short-term stabilisation policies are likely to be less effective.